Pengaruh Service Quality dan Perceived Value Terhadap Customer Satisfaction di Focus FitCabang Panam Pekanbaru - Sarah Pratiwi; Meyzi Heriyanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine the effect of service quality and perceived value on customer satisfaction at Focus Fit, Panam Pekanbaru Branch. This study will also show how these factors can influence customer satisfaction. Quantitative analysis techniques were used in this study by collecting data through questionnaires distributed to 89 active members of Focus Fit Members Panam Pekanbaru. Based on the results of multiple linear regression analysis, the results of the determination coefficient test indicate that service quality and perceived value have an 82.8% effect on customer satisfaction. The results also show that service quality and perceived value have a positive and significant impact partially and simultaneously on customer satisfaction of Focus Fit Members Panam Pekanbaru